MEMAKNAI KONSEP PENDAPATAN PADA KAMPUNG ADAT TUTHUBHADA KABUPATEN NAGEKEO, NTT - Pua Uda, Atikah Indawati; Leniwati, Driana (EL MUHASABA: Jurnal Akuntansi (e-Journal), 2022)
This studies is a case observe studies with a qualitative descriptive method which aims ti determine the understanding of the that means of the concept of profits in the Tuthubhada conventional village community. The object of his research is the Tuthubhada conventional village and the challenge of this studies is the Chairperson of POKDARWIS and the Tuthubhada traditional village community. resources of data used in this study are primary statistics and secondary records, information collection techniques use documentation and interviews, and statistics evaluation strategies the usage of documentation and interviews, and data analysis strategies is the evaluation strategies used is qulitative analysis with the aid of (1) describing the statistics acquired from interviews associated to traditional village earnings to growth network earnings, (2) describe the information received from interviews related to the which means of income in line with the Tuthubhada customary village network, (three) describe and analyze the which means of earnings seen from informants 1. Mr. Amandus Watu. Informant 2. Mr. Skarias Sela Nima, and informant three. Mrs.Beenadeta Wea. The result confirmed that the Tuthubhada traditional village community understood the that means of profits as 1) the which means of profits as income, 2) the that means of profits as an artwork channel, three) the which means of profits as gratitude.